Pre-eclampsia and Cardiovascular Disease: From Pregnancy to Postpartum - Veronica Giorgione; Matthew Cauldwell; Basky Thilaganathan (European Cardiology Review)
Hypertensive disorders of pregnancy (HDP) complicate approximately 10% of pregnancies. In addition to multiorgan manifestations related to endothelial dysfunction, HDP confers an increased risk of cardiovascular disease during delivery hospitalisation, such as heart failure, pulmonary oedema, acute MI and cerebrovascular events. However, the cardiovascular legacy of HDP extends beyond birth since these women are significantly more likely to develop cardiovascular risk factors in the immediate postnatal period and major cardiovascular disease in the long term. The main mediator of cardiovascular disease in women with a history of HDP is chronic hypertension, followed by obesity, hypercholesterolaemia and diabetes. Therefore, optimising blood pressure levels from the immediate postpartum period until the first months postnatally could have beneficial effects on the development of hypertension and improve long-term cardiovascular health. Peripartum screening based on maternal demographic, and clinical and echocardiographic data could help clinicians identify women with HDP at highest risk of developing postpartum hypertension who would benefit from targeted primary cardiovascular prevention.